2004
DOI: 10.1210/en.2003-1767
|View full text |Cite
|
Sign up to set email alerts
|

Antiapoptotic Effects of Leptin in Human Neuroblastoma Cells

Abstract: Many factors regulate nervous system development, including complex cross-talk between local neuroendocrine systems. The adipocyte-secreted hormone leptin, mainly known for its key roles in nutrition and reproductive balance, may also be involved in neuroanatomical organization, myelination processes, and neuronal/glia maturation. SK-N-SH-SY5Y neuroblastoma cells were employed as an in vitro model of human neuronal cells to determine whether leptin exerts neuroprotective activities. We show that SH-SY5Y cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
103
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(113 citation statements)
references
References 87 publications
8
103
1
Order By: Relevance
“…However, central regulation of leptin gene expression is different from that in the adipocytes. The co-localization of leptin and leptin receptors in multiple brain regions is consistent with reports that leptin regulates brain development, neuronal projections, and the expression of neuronal and glial proteins (Ahima et al 1999), and possesses both anti-apoptotic (Russo et al 2004) and neuroprotective properties (Dicou et al 2001). Leptin has also been shown to have mitogenic (Wolf et al 1999) and angiogenic activity (Sierra-Honigmann et al 1998) in a number of cell types.…”
Section: Introductionsupporting
confidence: 89%
“…However, central regulation of leptin gene expression is different from that in the adipocytes. The co-localization of leptin and leptin receptors in multiple brain regions is consistent with reports that leptin regulates brain development, neuronal projections, and the expression of neuronal and glial proteins (Ahima et al 1999), and possesses both anti-apoptotic (Russo et al 2004) and neuroprotective properties (Dicou et al 2001). Leptin has also been shown to have mitogenic (Wolf et al 1999) and angiogenic activity (Sierra-Honigmann et al 1998) in a number of cell types.…”
Section: Introductionsupporting
confidence: 89%
“…In contrast, Fujita et al demonstrated that leptin in fasted mice is able to prevent the apoptotic reduction of lymphocyte numbers in steroid-injected mice via a bcl-xL-dependent mechanism (12). This anti-apoptotic effect of leptin is in line with evidence that the hormone protects SK-N-SH-SY5Y neuroblastoma cells from apoptosis in serum-free medium by a STAT/JAK-dependent down regulation of caspase-10 and tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) (13). It is well known that leptin contributes to a physiological pregnancy by regulation of implantation, energy balance of placenta and conceptus, as well as an angiogenic factor (14 -16).…”
Section: Introductionsupporting
confidence: 67%
“…Indeed, leptin has been found to act as an anti-apoptotic hormone under stress conditions (Russo et al, 2004). A role for leptin in neurogenesis and neurodevelopment is strengthened by the observations of Udagaw and others (Udagawa et al, 2006) that leptin stimulates the proliferation of precursor cells committed to neuronal differentiation, and promotes neuronal terminal differentiation.…”
Section: Discussionmentioning
confidence: 97%